(untitled) (Journal of Economic Research & Business Administration, 2017)
Formation and development of small business is one of the priority directions of socio-economic policy of any state. An important component of small business is women’s entrepreneurship and business because in Kazakhstan women represent half of entrepreneurs. However, the number of unemployed women is 55.2%, so it is necessary to involve them in business and create conditions for socio-cultural adaptation of women in business and business.This will not only reduce female unemployment by creating small businesses, but will also ensure the dynamic development of small businesses.In this regard, the necessity of defining the gender structure of small women entrepreneurship and business in Kazakhstan is justified, a «segmented» approach to the study of women’s entrepreneurship and business is proposed, which will ensure the exact orientation of measures of state support for women’s business and business in Kazakhstan, increase their effectiveness, and ensure the growth of women’s entrepreneurship and business.